Facile, Regio- and Diastereoselective Synthesis of Spiro-Pyrrolidine and Pyrrolizine Derivatives and Evaluation of Their Antiproliferative Activities - Almansour, Abdulrahman I.; Kumar, Raju Suresh; Beevi, Farzana; Shirazi, Amir Nasrolahi; Osman, Hasnah; Ismail, Rusli; Tan, Soo Choon; Brian, Sullivan; Kellen, McCaffrey; Nahhas, Alaa; Parang, Keykavous; Ali, Mohamed Ashraf (MDPI, 2014)
A number of novel spiro-pyrrolidines/pyrrolizines derivatives were synthesized through [3+2]-cycloaddition of azomethine ylides with 3,5-bis[(E)- arylmethylidene]tetrahydro-4(1H)-pyridinones 2a–n. Azomethine ylides were generated in situ from the reaction of 1H-indole-2,3-dione (isatin, 3) with N-methylglycine (sarcosine), phenylglycine, or proline. All compounds (50 μM) were evaluated for their antiproliferative activity against human breast carcinoma (MDA-MB-231), leukemia lymphoblastic (CCRF-CEM), and ovarian carcinoma (SK-OV-3) cells. N-α-Phenyl substituted spiro-pyrrolidine derivatives (5a–n) showed higher antiproliferative activity in MDA-MB-231 than other cancer cell lines. Among spiro-pyrrolizines 6a–n, a number of derivatives including 6a–c and 6i–m showed a comparable activity with doxorubicin in all three cell lines. Among all compounds in three classes, 6a, 6b, and 6m, were found to be the most potent derivatives showing 64%, 87%, and 74% antiproliferative activity in MDA-MB-231, SK-OV-3, and CCRF-CEM cells, respectively. Compound 6b showed an IC50 value of 3.6 μM in CCRF-CEM cells. These data suggest the potential antiproliferative activity of spiro-pyrrolidines/pyrrolizines.